Estudio de factibilidad de incorporar microcomputadores a la empresa agrícola chilena. - Gálmez de P., José; Pittet D., Julio; Figueroa B., Eugenio; Barría P., Nelson; Astudillo C., Hugo; Delgado C., Enrique; Gálvez D., Judith; Poblete C., Julio (Monografías de Medicina Veterinaria, 1987)
-